A GESTÃO DA COMUNICAÇÃO MERCADOLÓGICA EM INSTITUIÇÕES DE ENSINO SUPERIOR CONFESSIONAIS – O CASO UMESP - Souza, Katia Cristina de (2016)
From the government of President Fernando Henrique Cardoso (1995-2003), there was incentive for opening new private higher education institutions in Brazil. Students become customers and start to choose the best option Institution of Higher Education (IES) that meets their needs. The aim of this work is to understand limits and control the development of marketing communication of IES in attracting new students. The research was developed from a descriptive exploratory study through literature review and qualitative research interviews with UMESP communication executives. The main results point to greater restriction on the development of marketing communication in the IES study (UMESP), notably the surveillance of the accuracy and scope of the advertising text